Les emplois du N fois en situation - Anne Marie Guiraud (Corela)
In French, the noun fois denotes a counting of occurrencies. It is used in a discourse to quantify the verbal group and to give an information on the number of iterations performed. We aim to demonstrate that the noun fois affects also the verbal aspect, and even can be enriched semantically depending on the contexts where it is used, until it can refer to an event. Therefore, we classify the main uses of the noun fois, considering whether it refers or not to an event, and show that there is a continuum in its ability to refer; we thus establish a base for a semantic and pragmatic study of the noun fois.